Pengaruh Lingkungan Kerja Terhadap Kinerja Karyawan di Hotel Fame Gading Serpong - Murni, Sartini; Ishak, Riani Prihatini (Jurnal Pariwisata, Bisnis dan Digital; Vol 2 No 2 (2026): Jurnal Pariwisata, Bisnis dan DigitalDO - 10.30647/jpbd.v2i2.2101, 2026)
This study aims to analyze the influence of the work environment on employee performance at Fame Hotel Gading Serpong. The study employed a quantitative approach with a descriptive-associative design and survey method. The population and sample consisted of all 53 employees of Fame Hotel Gading Serpong selected through saturated sampling. Primary data were collected using a five-point Likert-scale questionnaire, while secondary data were obtained from company documents and relevant literature. Data were analyzed using descriptive statistics, validity, reliability, normality, heteroscedasticity, autocorrelation, simple linear regression, t-test, and coefficient of determination with SPSS. The results show that the work environment has a positive and significant effect on employee performance, as indicated by a t-value of 11.331 and a significance value of 0.000. These findings emphasize the importance of managing physical and non-physical work environments as part of human resource management strategies in the hospitality industry. Keywords : employee performance, hospitality, human resource management, work environment